2008 3rd Petascale Data Storage Workshop 2008
DOI: 10.1109/pdsw.2008.4811885
|View full text |Cite
|
Sign up to set email alerts
|

Performance of RDMA-capable storage protocols on wide-area network

Abstract: Because of its high throughput, low CPU utilization, and direct data placement, RDMA (Remote Direct Memory Access) has been adopted for transport in a number of storage protocols, such as NFS and iSCSI. In this presentation, we provide a performance evaluation of RDMA-based NFS and iSCSI on Wide-Area Network (WAN). We show that these protocols, though benefit from RDMA on Local Area Network (LAN) and on WAN of short distance, are faced with a number of challenges to achieve good performance on long distance WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These evaluations rely on IB extension devices which limit WAN performance to approximately 8 Gbs, whereas our approach shows that RoCE can easily saturate existing 10G networks. Other related work has investigated RDMA-capable storage protocols over WANs [29] and explored system-level benefits of RDMA interfaces over 10G networks [9]. More recently there has been work to make a file transfer tool based on RDMA verbs [26].…”
Section: Related Workmentioning
confidence: 99%
“…These evaluations rely on IB extension devices which limit WAN performance to approximately 8 Gbs, whereas our approach shows that RoCE can easily saturate existing 10G networks. Other related work has investigated RDMA-capable storage protocols over WANs [29] and explored system-level benefits of RDMA interfaces over 10G networks [9]. More recently there has been work to make a file transfer tool based on RDMA verbs [26].…”
Section: Related Workmentioning
confidence: 99%
“…The one-sided semantics of RDMA READ/WRITE is a better choice for high-speed large-scale data transfer because it can decouple the data transfer entirely from the kernel software of the host operation system. Other researchers [17], [18] demonstrated that even though there are some benefits of using RDMA over LAN and WAN with short latency, there are challenges in achieving good performance in WAN with a long latency due to the problem of its low performance with RDMA READ operation. Based on these related works and their prior studies [16], [17], [18], our middleware is designed to exploit the full benefit of the RDMA by using RDMA WRITE operation yielding better performance and lower communication cost for synchronizing senders and receivers.…”
Section: Related Workmentioning
confidence: 99%
“…The work on NFS over RDMA demonstrates better performance [44] because of the benefits of RDMA in several scenarios. Several researchers [45], [46], [47], [35] have investigated various aspects of the performance characteristics over IB WAN.…”
Section: Related Workmentioning
confidence: 99%